Understanding the resilience of local seed systems: a case study of Uzumba-Maramba Pfungwe and Chimanimani Districts, Zimbabwe - Kusena, Kudzai (Department of Environmental and Geographical Science, 2022)
Globally, industrial crop production practices are of significant environmental concern, with some studies suggesting that smallholder farming systems could provide a more sustainable alternative. Local seed systems are at the core of smallholder agriculture and, although typically characterised as inefficient, can account for 60-100% of seed materials planted. Such systems are envisaged to remain as dominant seed sources in the foreseeable future, especially in the face of climate change and socio-economic challenges. However, there is a limited understanding of how local seed systems persist in the face of adversities. In this nexus, local seed systems are seen as key areas for enhancing resilience as they have strong links to food security and livelihoods in smallholder farming communities. Based on case studies from Zimbabwe, a country with more than 70% of its population dependent on smallholder agriculture, and a prolonged history of acute economic and ecological challenges, this study examines the concept of resilience in smallholder seed systems. The research aimed to explore interactions between the management of seed by smallholder farmers and social and ecological factors to understand their influence on the resilience of local seed systems. The history of local seed systems in Zimbabwe is explored, as well as the constraints faced by smallholder farmers and the innovations they have developed. The research characterises the activities of smallholder farmers and the quality of seeds circulating in local seed systems and examines how actors and institutions shape such characteristics. Building on critical theoretical debates around social-ecological systems, complex adaptive systems and resilience, an analysis is provided of how local seed systems interact with social and ecological factors, thus developing a conceptual understanding of how resilience is enabled or constrained in these systems. Case studies were selected in the Uzumba-Maramba-Pfungwe and Chimanimani Districts of Zimbabwe. Using an interdisciplinary research approach, qualitative and quantitative data collection methods were used, including household surveys, key informant interviews, participatory observations, and laboratory experiments. The findings show that history profoundly influences the social and ecological factors affecting local seed systems and informs how smallholder farmers have sustained these systems in the face of adversities. The innovations of smallholder farmers are emphasised alongside the repertoire of seed management options they used to respond to social and ecological adversities. Although traditional cultural practices to sustain local seed systems are waning, other forms of institutional arrangements driven by non-govenmental organisations are emerging, such as seed fairs, field days and community seed banks. These emergent activities have provided new platforms that promote local seed systems. Formal seed systems do not offer such opportunities, as they operate in a rigid, predetermined and highly regulated manner. However, an increased focus on local seed markets may conflict with traditional norms that view seeds as common heritage assets openly exchanged among farmers. A central premise is that local seed systems are shaped by non-linear and complex interactions of nested ecological and social factors. The demonstrated resilience behaviour of these systems challenges the appropriateness of prescriptive and mechanistic interventions such as seed aid. Ten key principles are proposed that characterise the resilience of local seed systems. The thesis emphasises the importance of integrating the principles into policy and practice to advance seed and food security of smallholder farmers.